2021
DOI: 10.1103/physreva.103.032613
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian phase sensitivity of boson-sampling-inspired strategies

Abstract: In this paper we study the phase sensitivity of generic linear interferometric schemes using Gaussian resources and measurements. Our formalism is based on the Fisher information. This allows us to separate the contributions of the measurement scheme, the experimental imperfections, and auxiliary systems. We demonstrate the strength of this formalism using a broad class of multimode Gaussian states that includes well-known results from single-and two-mode metrology scenarios. Using this, we prove that input co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Beyond losses and partial distinguishability, boson sampling has also been investigated under the effects of other sources of noise, such as fabrication imperfections 46 , 47 and Gaussian noise in the output data 48 . Finally, very recently, a tensor network approach for the simulation of noisy quantum circuits has been reported in Ref.…”
Section: Boson Sampling: Theoretical Overviewmentioning
confidence: 99%
“…Beyond losses and partial distinguishability, boson sampling has also been investigated under the effects of other sources of noise, such as fabrication imperfections 46 , 47 and Gaussian noise in the output data 48 . Finally, very recently, a tensor network approach for the simulation of noisy quantum circuits has been reported in Ref.…”
Section: Boson Sampling: Theoretical Overviewmentioning
confidence: 99%
“…For bosonic systems, it is indeed found that a close to optimal Heisenberg scaling is typically achieved. Valido and García-Ripoll (2021) explores the phase sensitivity of generic linear interferometric schemes using Gaussian resources and measurements, in what could be called bosonsampling-inspired strategies. Not quite making use of random bosonic quantum circuits, but rather introducing a new general technique that simplifies the construction of quantum Fourier transform using both path and polarization modes in linear optical interferometers, multi-photon interference in quantum Fourier transform circuits is experimentally studied in Su et al (2017).…”
Section: Exploiting Randomnessmentioning
confidence: 99%
“…Before moving on, one must mention other noteworthy approaches for optimal parameter estimation, including the Bayesian method [9,21] or boson-sampling inspired strategies [22].…”
Section: Introductionmentioning
confidence: 99%